Transit to the neoliberal economic model: The Political Constitution of 1991 and the new economic approach - Gil Pedreros, Ivon Dayann (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The neoliberal recommendations of the Washington Consensus were taken into account in the Political Constitution of 1991, however, in reality they had repercussions in the increase of the external public debt since the political and social conflict, as well as the backwardness of the national industry and dependence on coffee yields impeded long-term economic growth, increasing public spending and the need to resort to external credits